Peran Kepala Sekolah Sebagai Manajer dan Supervisor dalam Meningkatkan Kompetensi Guru di TK Pangudi Luhur Bernardus - Oetari, Veronica; Muhdi, Muhdi; Nurkolis, Nurkolis (PGRI Kota Semarang, 2024)
The formulation of this problem is 1) What is the role of the principal as a manager in increasing teacher competency at PL Bernardus Kindergarten, 2) What is the role of the principal as supervisor in increasing teacher competency at PL Bernardus Kindergarten. This research uses a descriptive qualitative approach. instrument. The instrument used in this research was an interview with informant principal, deputy principal, representatives of all teachers related to the role of Principal. Data analysis includes interview transcripts, data reduction, analysis, data interpretation and triangulation. Research results 1) The role of the principal as a manager in improving teacher competency at PL Bernardus Kindergarten Semarang. These include a) Planning (in the form of school coordination, planning time for program implementation, mapping teacher needs and problems, planning facilities and budget costs, b) Organizing (in the form of: grouping teachers according to tasks, dividing tasks according to work programs, organizing aspects of facilities equipment, dividing the budget based on needs and dividing the budget based on the principles of justice and transparency, c) Implementation (in the form of activating the school Learning Community, organizing and participating in In House Training (IHT), participating in PAUD Cluster activities, taking part in webinars, and writing scientific papers. and d) Supervision (internal supervision carried out by school principals and supervisors). 2) The role of the principal as a supervisor in increasing teacher competency at PL Bernardus Kindergarten Semarang. These include a) Supervision planning (includes: forming a supervisory team, making a supervision schedule, preparing supervision instruments, identifying problems, carrying out evaluations. b) Implementing supervision (first, pre-observation, then observation through class visits, assessment, providing guidance and direction ), and c) Follow-up (including direct coaching and indirect coaching). It is hoped that this research can develop existing competencies, especially competencies as managers and supervisors for school principals and can develop teacher competition Keyword : School Quality, Teacher Quality and Leadership